MINAT PEMBELIAN PRODUK KOSMETIK LOKAL DENGAN ULASAN ONLINE: KERANGKA KONSEPTUAL - Marsha Adilla Rahmani; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstract Nowadays women consider beauty as an important thing, women try to beautify themselves as much as possible, this is achieved by using several beauty products. This leads to increased demand and buying interest in beauty products such as makeup. The increasing demand for beauty products is the main driver of growth in the cosmetics industry. Revenue projections for local brand cosmetics sales in Indonesia are in the spotlight, in which case local cosmetics manufacturers are required to compete fiercely. To excel in this beauty industry competition, one of the main keys is to attract consumer buying interest. In this era of development, the audience is starting to be critical and looking for product or service information via the internet with online reviews and online ratings, this is expected to be an indicator in increasing purchase intention along with consumer perceptions formed from online reviews and online ratings. This study aims to determine the correlation and influence between Consumer Online Review and Consumer Online Rating on Purchase Intention through Consumer Perception using a causality quantitative research approach using SMART-PLS supporting software and using descriptive analysis techniques. The results state that online customer reviews and ratings have a positive and significant effect on purchasing decisions Arbaini (2020). Correlation analysis shows that there is a moderate and positive relationship between consumer perceptions and purchasing decisions (Sinaga et al., 2020). Keywords: Local Makeup Product, Online Review, Online Rating, Consumer Perception, Purchase Intention